Sodium fusidate-poly(D,L-lactide-co-glycolide) microspheres: Preparation, characterisation and in vivo evaluation of their effectiveness in the treatment of chronic osteomyelitis - DURMUŞOĞLU, LÜTFİYE (TAYLOR & FRANCIS LTD, 2007)
Purpose: The aim of this study was to prepare poly(D, L- lactide-co-glycolide) (PLGA) microspheres containing sodium fusidate ( SF) using a double emulsion solvent evaporation method with varying polymer: drug ratios (1: 1, 2.5: 1, 5: 1) and to evaluate its efficiency for the local treatment of chronic osteomyelitis. Methods: The particle size and distribution, morphological characteristics, thermal behaviour, drug content, encapsulation efficiency and in vitro release assessments of the formulations had been carried out. Sterilized SF-PLGA microspheres were implanted in the proximal tibia of rats with methicillin-resistant Staphylococcus aureus (MRSA) osteomyelitis. After 3 weeks of treatment, bone samples were analysed with a microbiological assay. Results: PLGA microspheres between the size ranges of 2.16-4.12 mu m were obtained. Production yield of all formulations was found to be higher than 79% and encapsulation efficiencies of 19.8-34.3% were obtained. DSC thermogram showed that the SF was in an amorphous state in the microspheres and the glass transition temperature ( Tg) of PLGA was not influenced by the preparation procedure. In vitro drug release studies had indicated that these microspheres had significant burst release and their drug release rates were decreased upon increasing the polymer: drug ratio (p < 0.05). Based on the in vivo data, rats implanted with SF-PLGA microspheres and empty microspheres showed 1987 +/- 1196 and 55526 +/- 49086 colony forming unit of MRSA in 1 g bone samples (CFU/g), respectively (p < 0.01).
Keywords: sodium fusidate; poly(D,L-lactide-co-glycolide) microspheres; emulsion solvent evaporation method; methicillin-resistant Staphylococcus aureus; chronic osteomyelitis; RESISTANT STAPHYLOCOCCUS-AUREUS; CIPROFLOXACIN IMPLANTS; BONE IMPLANTATION; FUSIDIC ACID; LACTIC-ACID; VITRO; MICROPARTICLES; FORMULATION; VANCOMYCIN; SIZE